2011
DOI: 10.3109/10715762.2010.550917
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin B elicits a glutathione antioxidant response and protects against apoptosis via the redox-sensitive ERK/Nrf2 pathway in AML12 hepatocytes

Abstract: This study examined the effects of (-)schisandrin B [(-)Sch B] on MAPK and Nrf2 activation and the subsequent induction of glutathione antioxidant response and cytoprotection against apoptosis in AML12 hepatocytes. Pharmacological tools, such as cytochrome P-450 (CYP) inhibitor, antioxidant, MAPK inhibitors and Nrf2 RNAi, were used to delineate the signalling pathway. (-)Sch B caused a time-dependent activation of MAPK in AML12 cells, particularly the ERK1/2. The MAPK activation was followed by an enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 36 publications
5
49
0
Order By: Relevance
“…The prooxidant-induced glutathione antioxidant response, as observed in the present study, is consistent with the recent findings in our laboratory that a low concentration of ROS arising from CYP-catalyzed metabolism of schisandrins can trigger the redox-sensitive signaling pathway, with resultant induction of Nrf2-activated expression of antioxidant proteins. 20) Taken together, results obtained from the present study support the postulation that prooxidants can invariably induce the glutathione antioxidant response and conferred cytoprotection against oxidant injury in vitro. Whether or not the prooxidant of interest can produce a similar response in vivo would depend on the bioavailability of the compound via oral route and the potential toxic effect of its prooxidant action.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The prooxidant-induced glutathione antioxidant response, as observed in the present study, is consistent with the recent findings in our laboratory that a low concentration of ROS arising from CYP-catalyzed metabolism of schisandrins can trigger the redox-sensitive signaling pathway, with resultant induction of Nrf2-activated expression of antioxidant proteins. 20) Taken together, results obtained from the present study support the postulation that prooxidants can invariably induce the glutathione antioxidant response and conferred cytoprotection against oxidant injury in vitro. Whether or not the prooxidant of interest can produce a similar response in vivo would depend on the bioavailability of the compound via oral route and the potential toxic effect of its prooxidant action.…”
Section: Discussionsupporting
confidence: 75%
“…It has been further demonstrated that the Sch B-induced glutathione antioxidant response is mediated via a ROS-dependent, redox-sensitive extracellular signalregulated kinase (ERK)/Nrf2/EpRE signal transduction pathway. 20) Curcumin is one of the principal curcuminoid obtained from the root of Curcuma longa, which was widely used in ancient Indian medicine for the treatment of various diseases, including liver disorders. Consistent with the traditional belief, curcumin has been shown to protect against the iron/CCl 4 -induced hepatotoxicity, 21,22) attenuate thioacetamide-induced hepatitis/cirrhosis 23,24) as well as to relieve the symptoms of cholestasis.…”
mentioning
confidence: 99%
“…The MAPK activation was followed by enhanced Nrf2 nuclear translocation and the elicitation of a glutathione-dependent anti-oxidant response in cultured hepatocytes and cardiomyocytes. 109,110 In addition, long-term SchB treatment by the oral route increased the expression of Hsp25 and Hsp70 in various rat tissues. 86 A recent study has shown that gomisin N (or ())SchB) enhanced tumour necrosis factor-a-induced apoptosis in Hela cells by suppressing NF-jB signalling.…”
Section: Pharmacological Actions Of Schbmentioning
confidence: 98%
“…The glutathione antioxidant system is regulated by nuclear factor erythroid 2-related factor-2 (Nrf2), the principal transcriptional regulator of cellular antioxidant genes, which in turn binds to its corresponding element, namely, the antioxidant response element (ARE), on DNA [100]. A recent study has elucidated the cytoprotective mechanism underlying the Sch-B-induced glutathione antioxidant response in cultured hepatocytes [101]. Sch B is metabolized by cytochrome P 450 with concomitant production of ROS [101].…”
Section: Hepatoprotective Action Of Sch B Against Nafldmentioning
confidence: 99%